Terapevtska ekvivalenca lokalno delujočih zdravil - Ekar, Petra (Farmacevtski vestnik, 2011)
Therapeutic equivalence of systemically acting medicinal products for human use is most often established by comparison of pharmacokinetic profiles for the test and the reference product. In case of locally acting medicinal products the presumption that plasma or urine profiles reflect the delivery to the site of action, is most often not appropriate. Other approaches used forestablishing therapeutic equivalence in that case are phase III clinical studies, pharmacodynamic studies, in vitro studies and other appropriate methods, depending on more or less specific regulatory requirements. Comparative clinical studies are, in contrast to pharmacokinetic (bioequivalence) studies which are most often connected to concept of therapeutic equivalence, larger, more time consuming, complex and costly.
Keywords: farmakodinamične študije; klinične študije; lokalno delujoča zdravila; študije in vitro; terapevtska ekvivalenca